Usefulness of the cytokines expression of Th1/Th2/Th17 and urinary CD80 excretion in adult-onset minimal change disease - Ping Chen; Yan Chen; Maoqing Jiang; Yijun Mo; Huanhuan Ying; Xun Tang; Jun Zhang (PeerJ, 2020)
Background Minimal change disease (MCD) is a common form of nephrotic syndrome in adults. However, the molecular mechanism underlying the pathogenesis of MCD remains incompletely understood. In this study, we aimed to investigate the role of the cytokines expression of Th1/Th2/Th17 and urinary CD80 excretion in adult-onset MCD patients. Methods The lymphocyte subsets, 34 cytokine levels of Th1/Th2/Th17, serum and urine concentrations of CD80, and expression of CD80 in glomeruli were analyzed in 28 cases (15 males and 13 females; average age: 34.1 years, age range: 18–56 years), including 10 patients with MCD in relapse, nine patients with MCD in remission and nine healthy controls. Results There was no significant difference of CD3+CD4+ cells proportion among patients with MCD in relapse, MCD in remission and healthy controls (P = 0.802). The cytokine levels of GM-CSF and tumor necrosis factor (TNF)-related activation-induced cytokine (TRANCE) in patients with MCD in relapse increased 1.5 times higher than those in remission. An evident increase in the excretion of urinary CD80 was found in patients with relapsed MCD compared with those in remission (598.4 ± 115.8 vs 81.78 ± 7.04 ng/g creatinine, P < 0.001) and healthy controls (598.4 ± 115.8 vs 67.44 ±  8.94  ng/g creatinine, P < 0.001). CD80 expression was observed in podocyte of MCD patient in relapse by immunofluorescence technique. Conclusions The cytokines GM-CSF and TRANCE are increased and the urinary CD80 levels are elevated in adult-onset MCD patients in relapse, indicating a disorder of Th1/Th2/Th17 balance and that the elevated excretion of CD80 may underlie the pathogenesis and development of adult-onset MCD.